Pendekatan Spiritual Religius Tindak Pidana Kekerasan Fisik terhadap Anak dan Perempuan dalam Rumah Tangga - Ibrahim, Aji Lukman; Kusuma, Aditama Candra; Rahmawati, Putri (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
The purpose of this study was to determine the permissibility of hitting children who do not pray and a nuzyus wife in Islamic law and to find out that violence against children and women in the household is associated with the values ​​contained in Pancasila. The results showed that although hitting children who do not pray and wives who are nuzyus in Islam is permissible, the Prophet SAW taught to treat children and wives with respect, compassion, and gentleness. Not by hitting arbitrarily when the wife and children make mistakes. Because in Islam, if you are going to hit you must pay attention to the conditions for hitting in Islam, it cannot be done arbitrarily. Domestic violence which is increasingly cruel day by day does not at all reflect the human values ​​contained in Pancasila, Some Indonesian people no longer understand the philosophical values ​​that should be a guide in social life and also guidelines for behavior, so that domestic violence that often occurs today does not reflect the real Indonesian people according to the ideals of the ancestors.